2012
DOI: 10.5539/jsd.v5n11p65
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Intangible Location Attributes on Residential Segregation in Jos, Nigeria

Abstract: Residential segregation could be regarded as a process whereby two or more distinct communities who formerly lived together separate from one another due to many factors. Residential segregation is not only applicable to small communities but rather to a larger region. As a result of the ongoing civil unrest that engulfed the city of Jos, there has been a process of residential mobility and relocation among people of different faith. The paper is aimed at examining the implication of intangible location attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…This was done by subjecting transactional data from 3,443 single-family houses to regression analysis and it was confirmed that on average investors systematically pay 13.23 per cent less than those residing in the houses (Larsen, 2010). Other studies supported location as one of the key determinants of residential property rental value (for example, Olujimi & Bello, 2009;Howley, 2009;Aliyu et al, 2012). In addition, locations do influence residential rental values through tangible or intangible mode as labelled by Aliyu et al (2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This was done by subjecting transactional data from 3,443 single-family houses to regression analysis and it was confirmed that on average investors systematically pay 13.23 per cent less than those residing in the houses (Larsen, 2010). Other studies supported location as one of the key determinants of residential property rental value (for example, Olujimi & Bello, 2009;Howley, 2009;Aliyu et al, 2012). In addition, locations do influence residential rental values through tangible or intangible mode as labelled by Aliyu et al (2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies supported location as one of the key determinants of residential property rental value (for example, Olujimi & Bello, 2009;Howley, 2009;Aliyu et al, 2012). In addition, locations do influence residential rental values through tangible or intangible mode as labelled by Aliyu et al (2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In another definition similar to that of Kemper, residential segregation is said to be the degree to which two or more groups live separately from one to another in different parts of the urban space (Aguilera & Ugalde, 2007). While Aliyu, et al (2012) opined that, it is the process where two or more communities that formerly lived together separate because of some factors. This they report could be because of either religious or ethnic reasons.…”
Section: Concept Of Residential Segregationmentioning
confidence: 99%
“…The negative stereo-types about the sabon gari and its inhabitants have been the cause of the incessant ethno-religious conflicts in Kano, and indeed many states in the country. These conflicts have in turn affected the sales and rental value of residential properties in the affected areas for instance in Jos (see Dung-Gwom, 2008Aliyu et al, 2012).…”
Section: Consequences Of Residential Segregation In Nigeriamentioning
confidence: 99%